Good governance and modern international financial institutions - Gao, Xuan; Quayle, Peter (AIIB yearbook of international law, 2019)
This first edition of the 'AIIB Yearbook of International Law' (AYIL), edited by Peter Quayle and Xuan Gao, is based upon the inaugural 2017 AIIB Legal Conference, both titled, 'Good Governance and Modern International Financial Institutions' (IFIs). Following a Preface by the General Counsel of the AIIB and General Editor of AYIL, Gerard Sanders, and an Introduction by the Editors, this edition of AYIL draws upon expertise from other IFIs, international law and governance practitioners, and eminent academics. It is divided into three parts to reflect a series of dimensions to the good governance of IFIs. Firstly, the role of the membership of IFIs as expressed through their executive governance organs. Second, the legal basis of governance of IFIs. And third, the interaction around governance between IFIs and external stakeholders.